The geology of Sierra Calderona (SE Iberian Cordillera, Spain), a review. Results of a new 1:25.000 scale geological mapping - Pedro Pablo Hernaiz-Huerta (Journal of Maps)
A new geological mapping of Sierra Calderona (SE Iberian Cordillera) has confirmed the widespread presence of the Muschelkalk M2 unit overlying a ubiquitous Muschelkalk M1 carbonate unit. Thus, the allocation of this range in the Levantine-Balearic Triassic Domain is not justified and a previous assignment of the entire Muschelkalk carbonate succession of this region to the M3 unit is untenable. Evidence of Permo-Triassic extensional tectonics by local unconformities separating Permian and Triassic units and a more widespread unconformity at the base of the Jurassic succession is recorded. Paleogene-Early Neogene compression-related structures associated with the formation of the NW-SE trending Sierra Calderona anticlinorium are scarce, but numerous detachment surfaces within the stratigraphic pile suggest a complex thick-skinned tectonics. The dominant tectonic grain in Sierra Calderona is a Neogene extensional structure with a preferential pattern of blocks stepping down to the coast, which is related to the opening of the Valencia Trough.